(untitled) (EAAE Annual Conference Proceedings, 2023)
Postgraduate professional practice courses (part 3) play a critical role in the registration process for Architects. However, there is little research published on the pedagogy of these courses nor their suitability to the evolving demands on the multifaceted role required of Architects today. As a result, there is a need to reassess Part 3 courses considering the meta-competencies required in Architect’s diverse ‘ways of practice.’